Validation of Essential Acoustic Parameters for Highly Urgent In-Vehicle Collision Warnings. (March 2018) - Lewis, Bridget A.; Eisert, Jesse L.; Baldwin, Carryl L.
Objective: The aim of this study was to validate the importance of key acoustic criteria for use as in-vehicle forward collision warning (FCW) systems. Background: Despite recent advances in vehicle safety, automobile crashes remain one of the leading causes of death. As automation allows for more control of noncritical functions by the vehicle, the potential for disengagement and distraction from the driving task also increases. It is, therefore, as important as ever that in-vehicle safety-critical interfaces are intuitive and unambiguous, promoting effective collision avoidance responses upon first exposure even under divided-attention conditions. Method: The current study used a driving simulator to assess the effectiveness of two warnings, one that met all essential acoustic parameters, one that met only some essential parameters, and a no-warning control in the context of a lead vehicle–following task in conjunction with a cognitive distractor task and collision event. Results: Participants receiving an FCW comprising five essential acoustic components had improved collision avoidance responses relative to a no-warning condition and an FCW missing essential elements on their first exposure. Responses to a consistently good warning (GMU Prime) improved with subsequent exposures, whereas continued exposure to the less optimal FCW (GMU Sub-Prime) resulted in poorer performance even relative to receiving no warning at all. Conclusions: This study provides support for previous warning design studies and for the validity of five key acoustic parameters essential for the design of effective in-vehicle FCWs. Application: Results from this study have implications for the design of auditory FCWs and in-vehicle display design.